Medicinal Potential of Flavonoids Extracted from The Leaves of Lippia multifora Moldenke: Review - Moussavou , Ortalie Jeancine Ouboura; Malonga , Archange Michel Emmanuel Mboungou; Miguel , Landry Martial; Lingomo , Berthrand Stéphane Wossolo; Moukassa, Donatien; Abena , Ange Antoine (International Journal of Pharmacology and Toxicology, 2025)
Flavonoids are natural pigments found throughout the plant kingdom. They are present in certain fruits, vegetables, drinks, plant-based foods, and medicinal plants. They form a large family of several natural compounds. They include flavanols, flavanones, isoflavones, flavonols, flavones, and anthocyanins. The organoleptic properties and therapeutic effects of flavonoids extracted from the leaves of Lippia multifora Moldenke have been the subject of numerous studies. Flavonoids extracted from Lippia multifora Moldenke leaves are claimed to be antioxidant, anti-allergic, anti-inflammatory, antimicrobial, and anti-carcinogenic. They are used in a wide range of sectors, including food processing, cosmetology, and the pharmaceutical industry.